Boosting zinc storage performance via conductive materials. (January 2021) - Ruan, Pengchao; Xu, Xilian; Feng, Jinxiu; Yu, Linhai; Gao, Xinlong; Shi, Wenhui; Wu, Fangfang; Liu, Wenxian; Zang, Xiaoxian; Ma, Fuyuan; Cao, Xiehong
Graphical abstract: This review summarizes the recent strategies for rational incorporation of cathode materials with conductive carbon-containing materials and their role in enhancing zinc storage performance. Highlights: Strategies of boosting zinc storage performance via conductive materials are introduced. The role of conductive materials in enhancing zinc storage performance is emphasized. The mechanism of improved zinc storage performance is discussed. The current challenges and future research directions are proposed. Abstract: Aqueous zinc ion batteries (ZIBs) are one of the most promising energy storage systems due to low cost, high safety and theoretical capacity. However, it is still a challenge to achieve high-performance aqueous ZIBs with long cycle life and high energy density because of low conductivity and poor structural stability of cathode materials. Conductive materials, such as carbon nanostructures, with good electrical conductivity, electrochemical stability and unique physical properties can combine with cathode materials to effectively improve the performance of aqueous ZIBs. In this review, the current strategies for rational incorporation of cathode materials with conductive materials, including carbon materials, conductive polymers and MXene, to achieve enhanced performance of ZIBs are summarized. The improved zinc storage performance for such hybrid cathode is also discussed in terms of microstructures and electrochemical reaction mechanism. Finally, we emphasize the essential role of conductive materials in enhancing zinc storage performance, and propose future research directions.